Application of geochemical modelling software as a tool to predict the diagenetic reactions between the marine connate water and the salt dome in a petroleum system. (August 2021) - Klunk, Marcos Antonio; Dasgupta, Sudipta; Das, Mohuli; Conceição, Rommulo Vieira; Siqueira Xavier, Soyane Juceli; Chemale, Farid; Wander, Paulo Roberto
Abstract: The field of geochemical modelling has developed rapidly since the early 1960s when the first attempts were made to predict the concentrations of dissolved chemical species in the seawater. Researchers have eventually realized the significance of predicting the behavior of different chemical elements in geological environments in order to understand the complexities of the chemical reactions. Henceforth, the construction of geochemical models based on numerical simulations with a set of empirical data, aims to predict the behavior of species. The constructed model is thereafter correlated with the existing geological evidence of the study area. Hereby, this work aims to generate a geochemical model capable of predicting the quality of hydrocarbon reservoirs by analyzing the diagenetic reactions between marine connate water and salt domes in a petroleum system. In order to achieve this goal, the software like PHREEQC™, GWB™ and TOUGHREACT™ (batch mode); GWB™ and TOUGHREACT™ in 1D have been used. The study area for this particular research was selected to be Gulf of Mexico where water-rock interactions occur within the turbidite reservoir of the petroleum system. Simulation results in "batch" mode at 25°C reveals the increasing saturation index of halite and sylvite. Dependening on the variable software, the steady-state has been achieved at different time interval. In low temperatures (25°C–100°C), there has been a convergence of results, while at higher temperatures (120°C–160°C), however, each software generates unique curve profiles. The 1D simulations of different geochemical modelling software display reproducibility of the results. Users must be cautious while selecting a specific geochemical modelling software with a simulator, which has a compatibale temperature range for the analyses. Highlights: Numerical modeling has gained great importance in the understanding of complex diagenetic processes. Kinetic, thermodynamic parameters of diagenetic reactions, allow model constructionto predict geochemistry of reservoir. Geochemical modelling software (PHREEQC™, GWB™ and TOUGHREACT™) were analyzed in "batch" mode simulation and 1D. Users must be cautious while selecting a geochemical modelling software, estimating the required temperature range.